KONSEP PEMBANGUNAN SUMBER DAYA MANUSIA PENDIDIKAN PERSPEKTIF IBNU SINA DAN RELEVANSINYA DALAM KONTEKS PENGEMBANGAN MASYARAKAT ISLAM - Haq RD, Amirul; Ichsan, Muhammad; Putra, Rahmad Syah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: Educational Human Resources are sources that play an active role in an educational institution in the process of creating qualified and competent graduates in their fields. This paper will examine the concept of developing educational resources from Ibn Sina's perspective and its relevance to the context of developing Islamic society. This article is a literature review with the sources used in consisting of primary data and secondary data. Primary data is the main source that is used as a reference in this writing, namely books or journals related to Ibn Sina's educational thoughts, and secondary data in the form of supporting sources related to education, development, and education. The data analysis technique uses the content analysis method with 4 stages, namely: 1) data classification; 2) data sorting; 3) leveraging/deepening data; and 4) Drawing conclusions. Based on the results of the study, it was found that the concept of development of Human Resources for Education in Ibn Sina's perspective is very relevant to the context of developing Islamic society today, he argues that the development of human resources for education is the first step that must be done directly or indirectly. Because educational human resources are closely related to efforts to prepare development education graduates for the community in the context of developing Islam by implementing a social system that has Islamic philosophical values (khaira ummah), which includes developing the abilities possessed by a human being, namely Spiritual which consists of reason, character and body which consists of limbs, through a process obtained during education.Keywords: Development; Human Resources; Education; Ibn Sina.Abstrak: Sumber Daya Manusia Pendidikan merupakan sumber yang berperan aktif terhadap jalannya suatu lembaga pendidikan dalam proses menciptakan lulusan yang bermutu dan berkompeten di bidangnya. Tulisan ini akan mengkaji tentang konsep pembangunan sumber daya manusia pendidikan perspektif Ibnu Sina dan relevansinya dengan konteks pengembangan masyarakat Islam. Artikel ini merupakan kajian kepustakaan dengan sumber yang digunakan dalam terdiri dari data Primer dan data sekunder. Data Primer berupa sumber utama yang menjadi rujukan dalam penulisan ini yaitu buku atau jurnal yang berkaitan dengan Pemikiran pendidikan Ibnu Sina, dan Data Sekunder berupa sumber pendukung yang berkaitan dengan pembangunan pendidikan, pembangunan, dan pendidikan. Adapun teknik analisis data menggunakan metode analisis konten dengan 4 jenis tahapan yaitu: 1) klasifikasi data; 2) pemilahan data; 3) verifikasi/pendalaman data; dan 4) penarikan kesimpulan. Berdasarkan hasil kajian diperoleh hasil bahwa dalam konsep pembangunan Sumber Daya Manusia Pendidikan dalam perspektif Ibnu Sina sangat relevan dengan konteks pengembangan masyarakat Islam saat ini, dirinya berpendapat bahwa pembangunan sumber daya manusia pendidikan merupakan langkah awal yang harus dilakukan secara langsung maupun tidak langsung. Karena pembangunan sumber daya manusia pendidikan berhubungan erat kepada upaya mempersiapkan lulusan lembaga pendidikan untuk mengabdi kepada masyarakat dalam rangka melakukan pengembangan masyarakat Islam dengan mengimplementasikan sistem kemasyarakatan yang memiliki nilai-nilai philosofis keislaman (khaira ummah), yang di dalamnya berupa pengembangan kemampuan-kemampuan yang dimiliki oleh seorang manusia yaitu Rohani yang terdiri dari akal, budi pekerti dan Jasmani yang terdiri dari anggota badan, melalui proses yang diperoleh selama pendidikan.Kata Kunci: Pembangunan; Sumber Daya Manusia; Pendidikan; Ibnu Sina.